Effects of standard breakfast on pharmacokinetics of oral zidovudine in patients with AIDS. - Ruhnke, M (1993)
The influence of a standard breakfast on the single-dose pharmacokinetics of zidovudine (AZT) after oral administration of 100 and 250 mg of AZT was studied in 27 subjects with advanced human immunodeficiency virus infection (Centers for Disease Control stage IV). Concentrations of AZT and the 5'-glucuronide metabolite (GAZT) in serum and urine were measured by a high-pressure liquid chromatographic method. Pharmacokinetic analysis was done by an open one-compartment model as well as noncompartmentally. The results were summarized as medians with 50% confidence ranges because of the high degree of interindividual variability. Peak levels in plasma were moderately reduced after administration of 100 mg AZT in the nonfasting group (1.79 mumol/liter in the fasting group [F], 1.12 mumol/liter in the group that received breakfast [B]) and were markedly reduced after administration of 250 mg AZT (6.51 mumol/liter [F], 1.79 mumol/liter [B]). The terminal half-life in plasma was prolonged almost twofold after breakfast with 100 and 250 mg of AZT (100 mg, 36.4 min [F] and 51.6 min [B]; 250 mg, 35.3 min [F] and 63.6 min [B]). Recoveries (AZT and GAZT) in urine varied with both dosages, reflecting more a problem of accounting for the metabolite GAZT in urine than a relevant difference (100 mg, 115% [F] and 76.5% [B]; 250 mg, 71% [F] and 99.4% [B]). Our data suggest that absorption of AZT in human immunodeficiency virus-infected subjects is extremely variable, with a high degree of interindividual differences. Furthermore, breakfast had a marked influence on the absorption of AZT, suggesting that the drug should be taken in a fasting state.